The politics of pixels: A review and agenda for critical remote sensing. (June 2022) - Bennett, Mia M; Chen, Janice K; Alvarez León, Luis F; Gleason, Colin J
We offer a review and research agenda for critical remote sensing, defined as inquiries and scientific practices cognizant of the embedding of power within the production, analysis, and instrumentalization of satellite imagery. First, we consider critiques of the satellite gaze. Second, we chronicle remote sensing's evolving political economy, examining the technology's use by governments, scientists, and commercial and non-governmental actors. Then, we review practices of critical remote sensing, categorized as research (1) exposing injustices; (2) engaging situated knowledges; and (3) empowering marginalized actors. Lastly, we suggest five areas for intertwining critiques and practices and consider possibilities for counter–remote sensing.